2012
DOI: 10.1371/journal.pone.0049893
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interplay between Rap1 and PKA Regulates Induction of Angiogenesis in Prostate Cancer

Abstract: Angiogenesis inhibition is an important therapeutic strategy for advanced stage prostate cancer. Previous work from our laboratory showed that sustained stimulation of Rap1 by 8-pCPT-2'-O-Me-cAMP (8CPT) via activation of Epac, a Rap1 GEF, or by expression of a constitutively active Rap1 mutant (cRap1) suppresses endothelial cell chemotaxis and subsequent angiogenesis. When we tested this model in the context of a prostate tumor xenograft, we found that 8CPT had no significant effect on prostate tumor growth al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
(58 reference statements)
0
23
0
Order By: Relevance
“…Activation of PKA signaling can not only attenuate VEGF signaling in physiological conditions by blocking Raf activation [21] or through their actions on pp60Src [23], but also prohibit VEGF-induced increase in vascular permeability during cancer progression [22]. Paradoxically, distinct from previous demonstration that PKA promotes VEGF secretion, PKA may inhibit VEGF production by antagonizing Rap1 to regulate tumorstromal induction of angiogenesis in prostate cancer [24]. Besides the inhibitory role of PKA on VEGF signaling, direct activation of PKA signaling can induce EC apoptosis, resulting in the inhibition of angiogenesis in vivo [25].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKA signaling can not only attenuate VEGF signaling in physiological conditions by blocking Raf activation [21] or through their actions on pp60Src [23], but also prohibit VEGF-induced increase in vascular permeability during cancer progression [22]. Paradoxically, distinct from previous demonstration that PKA promotes VEGF secretion, PKA may inhibit VEGF production by antagonizing Rap1 to regulate tumorstromal induction of angiogenesis in prostate cancer [24]. Besides the inhibitory role of PKA on VEGF signaling, direct activation of PKA signaling can induce EC apoptosis, resulting in the inhibition of angiogenesis in vivo [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PKA can inhibit Rap1-dependent angiogenesis, acting downstream of Rap1 (40). cAMP-dependent activation of Epac can regulate Rap1-dependent adhesion and migration (27,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of 007 were not affected by EPAC1 and EPAC2 silencing using siRNA, but could be rescued by PKA inhibitors H89 and PKI [59]. This is not completely surprising because while 007 exerts about 100-fold selectivity towards EPAC1 over PKA, it still has the ability to activate PKA directly.…”
Section: Epac1 In Cancer Cell Migration and Metastasismentioning
confidence: 94%
“…In prostate cancer, while some results suggest that EPAC1 promotes metastasis and proliferation [56][57][58], one study contradicts these results by showing that activation of EPAC1 by 007, an EPAC-selective agonist, inhibits migration and proliferation of human prostate carcinoma cells [46]. Subsequently, it has been shown that the inhibitory effect observed for EPAC1 in the aforementioned contradictory study was actually the result of PKA [56][57][58]; [46] a Subsequent study suggests that the apparent suppressive effect observed for EPAC1 may be attributed to PKA activation, as the EPAC-selective agonist used was shown to activate PKA [59].…”
Section: Epac1 In Cancer Cell Migration and Metastasismentioning
confidence: 95%